A Half Decade Reviews and Controller Design for the Bergman Diabetic Patient Model (Journal of Engineering, 2025)
With an emphasis on individuals with Type 1 diabetes, this study reviews blood glucose management techniques during the last five years. A brief introduction is provided to show how this biological issue turns out to be a control system issue in terms of plasma blood glucose management. This paper discusses new research on automated insulin delivery using the Bergman mathematical model. An attempt has been made to undertake a systematic review of the research that has been done so far in the development of artificial pancreas systems. The conclusion describes the development of a cognitive glucose-insulin controller and provides a fundamental grasp of how the nonlinear Bergman model for blood glucose regulation can be used to establish a control system for this biomedical control challenge. When compared to other current methods, the proposed cognitive controller shows a quicker response in terms of blood glucose maintenance. Additionally, the comparison results demonstrated that the suggested cognitive glucose-insulin control algorithm improved the time to reach a normal physiological blood glucose level for the first patient by 10% compared to the fuzzy logic and the fractional-order PID control algorithms, by 25% compared to the type-2 fuzzy control algorithm.